Visible-light-promoted sulfonylation of thiols with aryldiazonium and sodium metabisulphite leading to unsymmetrical thiosulfonates. Issue 11 (23rd March 2021) - Lv, Yufen; Luo, Jinyun; Ma, Yuchuan; Dong, Qi; He, Lin
Abstract : A facile visible-light-mediated protocol has been proposed for the synthesis of thiosulfonates via rhodamine 6G catalyzed sulfonylation of thiols with aryldiazonium and sodium metabisulphite at room temperature. Abstract : A new visible-light-mediated protocol has been proposed for the synthesis of thiosulfonates via metal-free sulfonylation of thiols with aryldiazonium and sodium metabisulphite at room temperature. This mild three-component reaction simply utilizes readily available rhodamine 6G as the photocatalyst and cheap inorganic sulfite of sodium metabisulfite as a SO2 surrogate and provides an attractive strategy to access various unsymmetrical thiosulfonates in moderate to good yields under oxidant- or strong acid-free conditions. Preliminary mechanistic studies indicated that a radical pathway was involved in the present transformation.